Method for constructing 3D BNm coated EP / EP-CNTs composite material through electrostatic direct writing type 3D printing method
The three-dimensional BNm@EP mesh structure is constructed through 3D printing technology and CNTs are added, which solves the interface thermal resistance problem caused by excessive thermal fillers, and achieves the effect of high thermal conductivity and prolongs service life.
Patent Information
- Application Number
- CN202411750120.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-14
AI Technical Summary
The excessive filling amount of thermally conductive filler leads to an increase in thermal resistance with the interface with the epoxy resin, resulting in difficulty in dissipating heat and low service life of electronic packaging products.
3D printing DIW direct writing technology is used to construct a three-dimensional BNm@EP mesh structure, and epoxy resin is impregnated with vacuum, and CNTs are added to improve thermal conductivity.
Achieve high thermal conductivity under a small amount of filler, reduce interface thermal resistance, extend the service life of electronic packaging materials, and improve their thermal conductivity.
Smart Images

Figure CN119431851A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electronic packaging technology, and in particular, relates to a method for constructing a 3DBN by an electrostatic direct writing 3D printing method. m @EP / EP-CNTs composite material method. Background Art
[0002] With the advent of the 5G era, electronic devices are developing rapidly in terms of integration and functionality. Electronic devices will generate a lot of heat inside at high power. If the heat is not dissipated in time, it will cause hidden dangers to the equipment. Therefore, the thermal management performance of electronic devices is one of the important factors restricting its development. The main materials of electronic devices are generally polymer composites, but their thermal conductivity is low. The thermal conductivity of epoxy resin is about 0.12W / (m·k). The thermal conductivity of polymer composites can be improved by adding ceramic fillers; however, excessive filling of thermal conductive fillers will increase the thermal resistance of the interface with epoxy resin, making heat dissipation difficult and shortening the service life of electronic packaging products. Summary of the invention
[0003] The problem to be solved by the present invention is that excessive filling amount of thermal conductive filler leads to increased thermal resistance at the interface with epoxy resin, which makes heat dissipation difficult and reduces the service life of electronic packaging products. Therefore, in order to achieve high thermal conductivity with a small amount of filler, the present invention uses 3D printing DIW direct writing technology to construct a three-dimensional BN m @EP mesh structure and vacuum impregnation with epoxy resin to prepare high thermal conductivity insulation composite materials. Reduce application restrictions in the field of electronic packaging.
[0004] The present invention uses 3D printing DIW direct writing technology to construct three-dimensional macro BN m @EP thermal conductive network, the present invention uses modified h-BN (BN m ), epoxy resin, photoinitiator, stir in dark to obtain printing ink. Then 3D printing DIW direct writing technology, using pressure extrusion, layer-by-layer stacking principle, UV curing, design and prepare three-dimensional BN m @EP thermal conductive network, vacuum impregnation of epoxy resin matrix and CNTs (carbon nanotubes) mixed glue with different mass fractions, and high thermal conductivity 3D BN is obtained after high temperature gradient curing m @EP / EP-CNTs composites. The addition of CNTs can reduce the flake BN m @EP network gaps, improve the orientation of the network structure, enhance the integrity of the thermal network, and CNTs themselves have high thermal conductivity, thereby further improving the thermal conductivity of the composite material; enhance the application potential in the field of electronic packaging materials. The method of the present invention prepares 3D printed BN m @EP thermal conductive network and epoxy resin composite materials are mainly used in the field of electronic packaging, electronic chip cooling system, and to improve the service life of electronic packaging insulation materials.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0006] The purpose of the present invention is to provide an electrostatic direct writing 3D printing method for constructing 3D BN m The method of @EP / EP-CNTs composite material specifically comprises the following steps:
[0007] Step 1: Stir epoxy resin, photoinitiator and diluent evenly under light-proof conditions, then add flake modified hexagonal boron nitride (BN m ), continue to stir in dark until uniform, to obtain slurry;
[0008] Step 2: Slowly inject the slurry prepared in step 1 into the syringe and degas.
[0009] Step 3: Install the degassed syringe on the 3D printer head, use direct ink writing (DIW) 3D printing technology to print and perform UV curing to obtain a three-dimensional mesh skeleton;
[0010] Step 5: Stir the epoxy resin and curing agent evenly in an oil bath at 60°C-80°C, then add the carbon nanotubes, continue stirring until evenly mixed, then add the accelerator, continue stirring, degas, and obtain a glue solution;
[0011] Step 6: Place the three-dimensional mesh skeleton in a preheated mold, quickly pour in the glue solution to immerse the skeleton in it, and after gradient heating and curing, obtain the composite material.
[0012] It is further defined that in step 1, the mass ratio of the epoxy resin, the photoinitiator, the diluent and the flake-shaped modified hexagonal boron nitride is 100:2:1:25.
[0013] It is further defined that in step one, the photoinitiator is a triarylsulfonium salt cationic photoinitiator 1176.
[0014] It is further defined that in step 1, the diluent is xylene.
[0015] Further defined, in step 1, the flake-shaped modified hexagonal boron nitride (BN m ) is obtained by modifying flake hexagonal boron nitride with octadecyltrimethylammonium bromide, and is prepared by a public method, with the following specific steps: Take an appropriate amount of deionized water and adjust it to pH = 9 with NaOH particles, measure 100 ml and add it to a three-necked flask, then add a certain amount of 10g h-BN and 0.06g OTAB (0.6wt% of h-BN) and stir at 80°C for 6 hours. Then filter the reaction solution, rinse it with deionized water 3 times, and vacuum dry it at 80°C for 24h to obtain the surface-treated modified h-BN powder, which is marked as BNm .
[0016] It is further defined that in step 2, the vacuum oven is used for degassing for 1h-2h.
[0017] It is further defined that in step three, the syringe is installed on the 3D printer head, the printing speed and the slurry extrusion speed are adjusted, the G code is loaded, and the set program is selected; the printer moves in the Z direction to print out a double-layer structure; the process parameters of the DIW 3D printing technology are: the inner diameter of the nozzle is 0.3mm, and the outer diameter of the nozzle is 0.56mm; the printing speed is 30mm / s; the layer thickness is 0.5mm; and the ambient temperature is room temperature.
[0018] It is further defined that in step three, the process parameters of ultraviolet light curing are: 300w light efficiency, 365nm wavelength.
[0019] It is further defined that the epoxy resin in step 1 and step 5 is bisphenol A epoxy resin E51.
[0020] It is further defined that in step five, the mass ratio of the epoxy resin to the curing agent is 100:72; the mass of the accelerator is 1% of the total mass of the epoxy resin and the curing agent.
[0021] It is further defined that in step five, the epoxy resin and the curing agent are stirred for 1 h to 3 h at a stirring rate of 1000 rpm.
[0022] It is further defined that in step five, the amount of carbon nanotubes used is 0% to 2wt% of the epoxy resin, and can be 0wt%, 1wt%, 1.5wt%, or 2wt%.
[0023] It is further defined that in step five, after adding the carbon nanotubes (CNTs), stirring is performed at a rate of 1000 rpm for 1 h to 3 h.
[0024] It is further defined that in step five, the curing agent is methylhexahydrophthalic anhydride.
[0025] It is further defined that in step five, the promoter is dimethylbenzylamine.
[0026] It is further defined that in step five, the stirring time after adding the accelerator is generally 10 minutes to 40 minutes, and the stirring rate is 1000 rpm.
[0027] It is further defined that in step five, degassing is carried out in a vacuum oven, and the degassing time is 0.5h-2h.
[0028] It is further defined that in step six, the mold preheating temperature is 60°C-80°C.
[0029] It is further defined that in step six, the gradient heating is carried out in an oven.
[0030] It is further defined that in step six, the gradient temperature rise curing is set as: curing at 80°C-100°C for 1.5 hours, heating to 120°C-130°C, curing for 1.5 hours, then heating to 140°C-160°C, curing for 2 hours.
[0031] The present invention also provides a composite material prepared by any of the above methods.
[0032] 3D BN prepared by the above method m @EP / EP-CNTs composite materials are mainly used in the field of electronic packaging to increase product service life.
[0033] The present invention solves the problem that the amount of thermal conductive filler is too large and the compatibility with the epoxy resin matrix is poor, the thermal conductivity increases while the interface thermal resistance increases, affecting the thermal conductivity and dielectric properties of the composite material, and limiting the application in the field of electronic packaging. The present invention constructs a thermal conductive filler with a three-dimensional thermal conductive network interlocking structure, which can greatly improve the thermal conductivity of the composite material and improve the service life of the electronic packaging material. m ), epoxy resin, and photoinitiator triarylsulfonium salt cationic photoinitiator 1176 are used as raw materials, and the printing ink is obtained by stirring in the dark. Then 3D printing DIW direct writing technology is used, and the three-dimensional BN is designed and prepared by using the principle of pressure extrusion, layer-by-layer stacking, and UV curing. m @EP thermal conductive network, vacuum impregnation epoxy resin matrix and CNTs (carbon nanotubes) mixed glue with different mass fractions, high thermal conductivity 3DBN is obtained after high temperature gradient curing m @EP / EP-CNTs composite material. 3D printing technology can effectively control the orientation structure of thermal conductive fillers. The addition of CNTs can reduce the gaps between the flaky h-BN networks, improve the orientation of the network structure, and enhance the integrity of the thermal conductive network. CNTs themselves have high thermal conductivity. The composite material of the present invention can improve thermal conductivity while maintaining certain dielectric properties. This new composite material is mainly used in the field of electronic packaging and has great potential to improve the service life of electronic packaging insulation materials.
[0034] BN prepared by 3D printing method according to the present invention m @EP network has a high degree of orientation and can form a continuous and complete thermal conductive network, which reduces the phenomenon of excessive interfacial voids caused by agglomeration and random dispersion between fillers, thereby improving the thermal conductivity of the composite material.
[0035] The present invention uses BN prepared by 3D printing method m@EP network prepares high thermal conductivity epoxy resin matrix composite materials, in which CNTs are added and mixed with epoxy resin, so that when impregnated with epoxy resin matrix glue, CNTs are filled into the flake modified h-BN (BN m ) gaps, enhancing the orientation structure of the thermal conductive network while improving the thermal conductivity and reducing the thermal expansion coefficient of the composite material, thus having good electrical insulation properties.
[0036] In order to further understand the features and technical contents of the present invention, please refer to the following detailed description and drawings of the present invention. However, the attached drawings are only provided for reference and illustration and are not intended to limit the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is 3D-BN m @Physical picture of EP / EP-CNTs composite material;
[0038] Figure 2 It's BN m @EP network structure scanning morphology;
[0039] Figure 3 3D-BN with different carbon nanotube (CNTs) contents m @Schematic diagram of scanning electron microscopy cross-section of EP / EP-CNTs composite material.
[0040] Figure 4 It is EP and BN m @Thermal conductivity diagram of EP / EP-CNTs composites;
[0041] Figure 5 It is the thermogravimetric analysis diagram of EP composite material;
[0042] Figure 6 It's BN m @Thermogravimetric analysis of EP / EP-CNTs composites;
[0043] Figure 7 Yes and BN m @Differential scanning calorimetry analysis diagram of EP / EP-CNTs composite materials;
[0044] Figure 8 It is EP and BN m @Infrared thermal imaging of EP / EP-CNTs composite materials;
[0045] Fig. 9 It is EP and BN m @Infrared thermal imaging curve of EP / EP-CNTs composite material;
[0046] Fig.10 It is EP and BN m@ Dielectric properties of EP / EP-CNTs composites: Dielectric constant diagram;
[0047] Fig.11 It is EP and BN m @ Dielectric properties of EP / EP-CNTs composites: dielectric loss diagram;
[0048] Fig.12 It is EP and BN m @Breakdown field strength diagram of EP / EP-CNTs composite material. DETAILED DESCRIPTION
[0049] The present invention will be described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, and do not limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.
[0050] The following examples used Flake modified hexagonal boron nitride (BN m ) wherein the modifier is octadecyltrimethylammonium bromide; Flake modified hexagonal boron nitride (BN m ) is prepared by the following steps:
[0051] Take an appropriate amount of deionized water and adjust the pH to 9 with NaOH pellets, take 100 ml and add it to a three-necked flask, then add a certain amount of 10 g h-BN and 0.06 g OTAB (0.6 wt% of h-BN) and stir at 80 ° C for 6 hours. Then filter the reaction solution, rinse it with deionized water 3 times, and vacuum dry it at 80 ° C for 24 hours to obtain the surface-treated modified h-BN powder, which is marked as BN m .
[0052] Embodiment 1:
[0053] In this embodiment, the electrostatic direct writing 3D printing method is used to construct 3D BN m The method of the @EP / EP-CNTs composite material is accomplished by the following steps:
[0054] Step 1: 20g bisphenol A epoxy resin E-51, 0.4g photoinitiator (triarylsulfonium salt cationic photoinitiator 1176), 0.2g diluent xylene, stir evenly at a stirring rate of 1000rpm in the dark (taking 1h), and then add 5g flake modified hexagonal boron nitride (BN m ), and stirred in the dark at a stirring rate of 1000 rpm for 3 h until the particles were uniformly dispersed therein to obtain a slurry.
[0055] Step 2: Slowly inject the slurry prepared in step 1 into a 10 ml syringe and place it in a vacuum drying oven for 1 hour for degassing.
[0056] Step 3: Install the syringe in step 2 on the 3D printer head, use direct ink writing (DIW) 3D printing technology to print and perform UV curing at the same time, adjust the printing speed and slurry extrusion speed, load the G code, and select the set program; the printer moves in the Z direction; at room temperature, the material is extruded from the syringe and deposited layer by layer on the XY motion table to replicate the digital model at a certain printing speed; set the single layer liquid thickness to 1mm, and print a double layer structure to obtain a three-dimensional mesh skeleton (such as Figure 1 and Figure 2 shown).
[0057] In step three, the process parameters of DIW 3D printing technology are: inner diameter of the nozzle: 0.3mm, outer diameter: 0.56mm; printing speed is 30mm / s; layer thickness is 0.5mm; experimental environment: room temperature.
[0058] Step 5: Add 20g of bisphenol A epoxy resin E-51 and 14.4g of curing agent methyl hexahydrophthalic anhydride into a three-necked flask at the same time, and stir in an oil bath at 60℃±2℃ for 3h; then add 1wt% of carbon nanotubes, stir in an oil bath at 60℃±2℃ for 3h, then add 0.03g of accelerator nitrogen-nitrogen dimethylbenzylamine, stir for 10 minutes, and move to a vacuum oven for degassing for 1h.
[0059] Step 6: Place the three-dimensional mesh skeleton in a preheated mold (the mold preheating temperature is 60°C ± 2°C), quickly pour in the glue solution to immerse the skeleton therein, and after gradient heating and curing, obtain the composite material.
[0060] Among them, the gradient temperature curing setting of step six is: curing at 80°C for 1.5 hours, heating to 120°C, curing for 1.5 hours, and then heating to 140°C and curing for 2 hours.
[0061] Embodiment 2:
[0062] In this embodiment, the electrostatic direct writing 3D printing method is used to construct 3D BN m The method of the @EP / EP-CNTs composite material is accomplished by the following steps:
[0063] Step 1: 20g bisphenol A epoxy resin E-51, 0.2g photoinitiator (triarylsulfonium salt cationic photoinitiator 1176), 0.2g diluent xylene, stir evenly at a stirring rate of 1000rpm in the dark (taking 1h), and then add 5g flake modified hexagonal boron nitride (BN m ), and stirred in the dark at a stirring rate of 1000 rpm for 3 h until the particles were uniformly dispersed therein to obtain a slurry.
[0064] Step 2: Slowly inject the slurry prepared in step 1 into a 10 ml syringe and place it in a vacuum drying oven for 1 hour for degassing.
[0065] Step 3: Install the syringe in step 2 on the 3D printer head, use direct ink writing (DIW) 3D printing technology to print and perform UV curing at the same time, adjust the printing speed and slurry extrusion speed, load the G code, and select the set program; the printer moves in the Z direction; at room temperature, the material is extruded from the syringe and deposited layer by layer on the XY motion table to replicate the digital model at a certain printing speed; set the single layer liquid thickness to 1mm, and print a double layer structure to obtain a three-dimensional mesh skeleton (such as Figure 1 and Figure 2 shown).
[0066] In step three, the process parameters of DIW 3D printing technology are: inner diameter of the nozzle: 0.3mm; outer diameter: 0.56mm; printing speed is 30mm / s; layer thickness is 0.5mm; experimental environment: room temperature.
[0067] Step 5: Add 20g of bisphenol A epoxy resin E-51 and 14.4g of curing agent methyl hexahydrophthalic anhydride into a three-necked flask at the same time, and stir in an oil bath at 60℃±2℃ for 3h; then add 1wt% of carbon nanotubes, stir in an oil bath at 60℃±2℃ for 3h, then add 0.03g of accelerator nitrogen-nitrogen dimethylbenzylamine, stir for 10 minutes, and move to a vacuum oven for degassing for 1h.
[0068] Step 6: Place the three-dimensional mesh skeleton in a preheated mold (the mold preheating temperature is 60°C ± 2°C), quickly pour in the glue solution to immerse the skeleton therein, and after gradient heating and curing, obtain the composite material.
[0069] Among them, the gradient temperature curing setting of step six is: curing at 80°C for 1.5 hours, heating to 120°C, curing for 1.5 hours, and then heating to 140°C and curing for 2 hours.
[0070] Embodiment 3:
[0071] In this embodiment, the electrostatic direct writing 3D printing method is used to construct 3D BN m The method of the @EP / EP-CNTs composite material is accomplished by the following steps:
[0072] Step 1: 20g bisphenol A epoxy resin E-51, 0.4g photoinitiator (triarylsulfonium salt cationic photoinitiator 1176), 0.2g diluent xylene, stir evenly at a stirring rate of 1000rpm in the dark (taking 1h), and then add 5g flake modified hexagonal boron nitride (BN m), and stirred in the dark at a stirring rate of 1000 rpm for 3 h until the particles were uniformly dispersed therein to obtain a slurry.
[0073] Step 2: Slowly inject the slurry prepared in step 1 into a 10 ml syringe and place it in a vacuum drying oven for 1 hour for degassing.
[0074] Step 3: Install the syringe in step 2 on the 3D printer head, use direct ink writing (DIW) 3D printing technology to print and perform UV curing at the same time, adjust the printing speed and slurry extrusion speed, load the G code, and select the set program; the printer moves in the Z direction; at room temperature, the material is extruded from the syringe and deposited layer by layer on the XY motion table to replicate the digital model at a certain printing speed; set the single layer liquid thickness to 1mm, and print a double layer structure to obtain a three-dimensional mesh skeleton (such as Figure 1 and Figure 2 shown).
[0075] In step three, the process parameters of DIW 3D printing technology are: inner diameter of the nozzle: 0.3mm; outer diameter: 0.56mm; printing speed is 30mm / s; layer thickness is 0.5mm; experimental environment: room temperature.
[0076] Step 5: Add 20g of bisphenol A epoxy resin E-51 and 14.4g of curing agent methyl hexahydrophthalic anhydride into a three-necked flask at the same time, and stir in an oil bath at 60℃±2℃ for 3h; then add 1.5wt% of carbon nanotubes, stir in an oil bath at 60℃±2℃ for 3h, then add 0.03g of accelerator nitrogen-nitrogen dimethylbenzylamine, stir for 10 minutes, and move to a vacuum oven for degassing for 1h.
[0077] Step 6: Place the three-dimensional mesh skeleton in a preheated mold (the mold preheating temperature is 60°C ± 2°C), quickly pour in the glue solution to immerse the skeleton therein, and after gradient heating and curing, obtain the composite material.
[0078] Among them, the gradient temperature curing setting of step six is: curing at 80°C for 1.5 hours, heating to 120°C, curing for 1.5 hours, and then heating to 140°C and curing for 2 hours.
[0079] Embodiment 4:
[0080] In this embodiment, the electrostatic direct writing 3D printing method is used to construct 3D BN m The method of the @EP / EP-CNTs composite material is accomplished by the following steps:
[0081] Step 1: 20g bisphenol A epoxy resin E-51, 0.4g photoinitiator (triarylsulfonium salt cationic photoinitiator 1176), 0.2g diluent xylene, stir evenly at a stirring rate of 1000rpm in the dark (taking 1h), and then add 5g flake modified hexagonal boron nitride (BN m ), and stirred in the dark at a stirring rate of 1000 rpm for 3 h until the particles were uniformly dispersed therein to obtain a slurry.
[0082] Step 2: Slowly inject the slurry prepared in step 1 into a 10 ml syringe and place it in a vacuum drying oven for 1 hour for degassing.
[0083] Step 3: Install the syringe in step 2 on the 3D printer head, use direct ink writing (DIW) 3D printing technology to print and perform UV curing at the same time, adjust the printing speed and slurry extrusion speed, load the G code, and select the set program; the printer moves in the Z direction; at room temperature, the material is extruded from the syringe and deposited layer by layer on the XY motion table to replicate the digital model at a certain printing speed; set the single layer liquid thickness to 1mm, and print a double layer structure to obtain a three-dimensional mesh skeleton (such as Figure 1 and Figure 2 shown).
[0084] In step three, the process parameters of DIW 3D printing technology are: inner diameter of the nozzle: 0.3mm; outer diameter: 0.56mm; printing speed is 30mm / s; layer thickness is 0.5mm; experimental environment: room temperature.
[0085] Step 5: Add 20g of bisphenol A epoxy resin E-51 and 14.4g of curing agent methyl hexahydrophthalic anhydride into a three-necked flask at the same time, and stir in an oil bath at 60℃±2℃ for 3h; then add 2wt% of carbon nanotubes, stir in an oil bath at 60℃±2℃ for 3h, then add 0.03g of accelerator nitrogen-nitrogen dimethylbenzylamine, stir for 10 minutes, and move to a vacuum oven for degassing for 1h.
[0086] Step 6: Place the three-dimensional mesh skeleton in a preheated mold (the mold preheating temperature is 60°C ± 2°C), quickly pour in the glue solution to immerse the skeleton therein, and after gradient heating and curing, obtain the composite material.
[0087] Among them, the gradient temperature curing setting of step six is: curing at 80°C for 1.5 hours, heating to 120°C, curing for 1.5 hours, and then heating to 140°C and curing for 2 hours.
[0088] Embodiment 5:
[0089] In this embodiment, the electrostatic direct writing 3D printing method is used to construct 3D BN m The method of the @EP / EP-CNTs composite material is accomplished by the following steps:
[0090] Step 1: 20g bisphenol A epoxy resin E-51, 0.4g photoinitiator (triarylsulfonium salt cationic photoinitiator 1176), 0.2g diluent xylene, stir evenly at a stirring rate of 1000rpm in the dark (taking 1h), and then add 5g flake modified hexagonal boron nitride (BN m ), and stirred in the dark at a stirring rate of 1000 rpm for 3 h until the particles were uniformly dispersed therein to obtain a slurry.
[0091] Step 2: Slowly inject the slurry prepared in step 1 into a 10 ml syringe and place it in a vacuum drying oven for 1 hour for degassing.
[0092] Step 3: Install the syringe in step 2 on the 3D printer head, use direct ink writing (DIW) 3D printing technology to print and perform UV curing at the same time, adjust the printing speed and slurry extrusion speed, load the G code, and select the set program; the printer moves in the Z direction; at room temperature, the material is extruded from the syringe and deposited layer by layer on the XY motion table to replicate the digital model at a certain printing speed; set the single layer liquid thickness to 1mm, and print a double layer structure to obtain a three-dimensional mesh skeleton (such as Figure 1 and Figure 2 shown).
[0093] In step three, the process parameters of DIW 3D printing technology are: inner diameter of the nozzle: 0.3mm; outer diameter: 0.56mm; printing speed is 30mm / s; layer thickness is 0.5mm; experimental environment: room temperature.
[0094] Step 5: Add 20g of bisphenol A epoxy resin E-51 and 14.4g of curing agent methyl hexahydrophthalic anhydride into a three-necked flask at the same time, and stir in an oil bath at 60℃±2℃ for 3h; then add 1wt% of carbon nanotubes, stir in an oil bath at 60℃±2℃ for 3h, then add 0.03g of accelerator nitrogen-nitrogen dimethylbenzylamine, stir for 10 minutes, and move to a vacuum oven for degassing for 1h.
[0095] Step 6: Place the three-dimensional mesh skeleton in a preheated mold (the mold preheating temperature is 60°C ± 2°C), quickly pour in the glue solution to immerse the skeleton therein, and after gradient heating and curing, obtain the composite material.
[0096] Among them, the gradient temperature curing setting of step six is: curing at 80°C for 1.5 hours, heating to 130°C, curing for 1.5 hours, and then heating to 160°C and curing for 2 hours.
[0097] Embodiment 6:
[0098] In this embodiment, the electrostatic direct writing 3D printing method is used to construct 3D BN mThe method of the @EP / EP-CNTs composite material is accomplished by the following steps:
[0099] Step 1: 20g bisphenol A epoxy resin E-51, 0.4g photoinitiator (triarylsulfonium salt cationic photoinitiator 1176), 0.2g diluent xylene, stir evenly at a stirring rate of 1000rpm in the dark (taking 1h), and then add 5g flake modified hexagonal boron nitride (BN m ), and stirred in the dark at a stirring rate of 1000 rpm for 3 h until the particles were uniformly dispersed therein to obtain a slurry.
[0100] Step 2: Slowly inject the slurry prepared in step 1 into a 10 ml syringe and place it in a vacuum drying oven for 1 hour for degassing.
[0101] Step 3: Install the syringe in step 2 on the 3D printer head, use direct ink writing (DIW) 3D printing technology to print and perform UV curing at the same time, adjust the printing speed and slurry extrusion speed, load the G code, and select the set program; the printer moves in the Z direction; at room temperature, the material is extruded from the syringe and deposited layer by layer on the XY motion table to replicate the digital model at a certain printing speed; set the single layer liquid thickness to 1mm, and print a double layer structure to obtain a three-dimensional mesh skeleton (such as Figure 1 and Figure 2 shown).
[0102] In step three, the process parameters of DIW 3D printing technology are: inner diameter of the nozzle: 0.3mm; outer diameter: 0.56mm; printing speed is 30mm / s; layer thickness is 0.5mm; experimental environment: room temperature.
[0103] Step 5: Add 20g of bisphenol A epoxy resin E-51 and 14.4g of curing agent methyl hexahydrophthalic anhydride into a three-necked flask at the same time, and stir in an oil bath at 60℃±2℃ for 3h; then add 0.03g of accelerator nitrogen-nitrogen dimethylbenzylamine, stir for 10 minutes, and move to a vacuum oven for degassing for 1h.
[0104] Step 6: Place the three-dimensional mesh skeleton in a preheated mold (the mold preheating temperature is 60°C ± 2°C), quickly pour in the glue solution to immerse the skeleton therein, and after gradient heating and curing, obtain the composite material.
[0105] Among them, the gradient temperature curing setting of step six is: curing at 80°C for 1.5 hours, heating to 120°C, curing for 1.5 hours, and then heating to 140°C and curing for 2 hours.
[0106] Embodiment 7:
[0107] In this embodiment, the electrostatic direct writing 3D printing method is used to construct 3D BN mThe method of the @EP / EP-CNTs composite material is accomplished by the following steps:
[0108] Step 1: 40g of bisphenol A epoxy resin E-51, 1.2g of photoinitiator (triarylsulfonium salt cationic photoinitiator 1176), and 0.4g of diluent xylene were stirred evenly at a stirring rate of 1000rpm in the dark (taking 1h), and then 5g of flake modified hexagonal boron nitride (BN m ), and stirred in the dark at a stirring rate of 1000 rpm for 3 h until the particles were uniformly dispersed therein to obtain a slurry.
[0109] Step 2: Slowly inject the slurry prepared in step 1 into a 10 ml syringe and place it in a vacuum drying oven for 1 hour for degassing.
[0110] Step 3: Install the syringe in step 2 on the 3D printer head, use direct ink writing (DIW) 3D printing technology to print and perform UV curing at the same time, adjust the printing speed and slurry extrusion speed, load the G code, and select the set program; the printer moves in the Z direction; at room temperature, the material is extruded from the syringe and deposited layer by layer on the XY motion table to replicate the digital model at a certain printing speed; set the single layer liquid thickness to 1mm, and print a double layer structure to obtain a three-dimensional mesh skeleton (such as Figure 1 and Figure 2 shown).
[0111] In step three, the process parameters of DIW 3D printing technology are: inner diameter of the nozzle: 0.3mm; outer diameter: 0.56mm; printing speed is 30mm / s; layer thickness is 0.5mm; experimental environment: room temperature.
[0112] Step 5: Add 20g of bisphenol A epoxy resin E-51 and 14.4g of curing agent methyl hexahydrophthalic anhydride into a three-necked flask at the same time, and stir in an oil bath at 60℃±2℃ for 3h; then add 1wt% of carbon nanotubes, stir in an oil bath at 60℃±2℃ for 3h, then add 0.03g of accelerator nitrogen-nitrogen dimethylbenzylamine, stir for 10 minutes, and move to a vacuum oven for degassing for 1h.
[0113] Step 6: Place the three-dimensional mesh skeleton in a preheated mold (the mold preheating temperature is 60°C ± 2°C), quickly pour in the glue solution to immerse the skeleton therein, and after gradient heating and curing, obtain the composite material.
[0114] Among them, the gradient temperature curing setting of step six is: curing at 80°C for 1.5 hours, heating to 120°C, curing for 1.5 hours, and then heating to 140°C and curing for 2 hours.
[0115] 3D-BN with different carbon nanotube (CNTs) contents m@SEM diagram of the cross section of EP / EP-CNTs composite material Figure 3 shown by Figure 3 It can be seen that a is impregnated with pure EP, and it can be seen that the interface contact between the three-dimensional strip structure and EP is complete; the structure in b and d is not obvious, the impregnation is insufficient and uneven, resulting in agglomeration; c is filled with 1.5wt% CNTs in epoxy resin, and it can be seen that the obvious strip structure and the morphological characteristics of the impregnated EP and CNTs can be seen. Therefore, the 3D printing method is successful in constructing a thermal conductive network, and 3D-BN m @EP / EP-1.5wt% CNTs composite material has the clearest network structure and complete interface contact with epoxy resin, which reduces thermal resistance and has the highest thermal conductivity.
[0116] EP and BN m @EP / EP-CNTs composite thermal conductivity diagram Figure 4 shown by Figure 4 It can be seen that with the increase of filling amount, 3D-BN m The thermal conductivity of the @EP / EP-CNTs composite material also increases. 3D printing technology constructs a macroscopic three-dimensional thermal conductive skeleton, forming a continuous heat transfer channel and enhancing the BN m The good interface compatibility between the thermally conductive particles and the epoxy resin matrix reduces phonon scattering, thereby improving the thermal conductivity of the composite material. CNTs have a very high thermal conductivity. Adding a small amount of mixed epoxy resin and impregnating it into the thermal conductive network can not only improve the thermal conductivity and thermal stability, but also play a role in microscopic support for the internal skeleton. The thermal conductivity of EP is 0.12W / (m·k), 25wt% w-BN m The thermal conductivity of / EP is 0.746; 3D-BN at 0wt% m @EP / EP-0wt%CNTs thermal conductivity is 0.748W / (m·k), 3D-BN at 2wt% m @EP / EP-2wt% CNTs thermal conductivity is 1.22W / (m·k). Therefore, it can be concluded that 3D printing can effectively improve the thermal conductivity of epoxy resin composite materials, and the three-dimensional thermal conductive network constructed from a macroscopic perspective can also improve the heat dissipation performance.
[0117] BN m @Thermogravimetric analysis of EP / EP-CNTs composites Figure 5 , 6 As shown: It can be seen that pure EP and 3D-BN m @EP / EP-CNTs composite materials have excellent heat resistance. EP and 3D-BN m@EP / EP-CNTs composite materials do not undergo thermal decomposition, and their initial decomposition temperatures are all above 300°C. When the temperature reaches about 380°C, EP and 3D-BN m @EP / EP-CNTs composite material has the fastest thermal decomposition rate; when the temperature reaches 800℃, due to the 3D-BN m @EP / EP-CNTs composite materials contain inorganic ceramic thermal conductive particles (BN m No thermal decomposition occurs below 800°C) and a trace amount of CNTs filler, so the amount of its thermal decomposition products is greater than that of pure EP.
[0118] BN m @EP / EP-CNTs composite material differential scanning calorimetry analysis diagram Figure 7 shown by Figure 7 It can be seen that the glass transition temperature (Tg) of the EP composite material in the DSC curve is about 132.61℃, because BN m The addition of fillers will hinder the movement and relaxation process of the EP cured cross-linked network, and 3D-BN m @EP / EP-CNTs composites have the same content of BN m , so 3D-BN m @The Tg value of EP / EP-CNTs composite materials is improved overall, and the CNTs filler content is less, so the overall Tg value is basically similar. 3D-BN m @EP / EP-CNTs composite materials have good thermal stability.
[0119] EP and BN m @EP / EP-CNTs composite material infrared thermal imaging picture Figure 8 , 9 Shown: EP, 3D-BN of the same size (0wt%-2wt%) m @EP / EP-CNTs composite samples were heated on a heating table at 20-60°C for 0, 10, 20, 30, 40, and 50 seconds. At the same time, according to the recorded changes, 2wt% w-BN m The temperature of / EP reaches 60°C after 40 seconds. With the increase of CNTs content, the temperature rises faster, the thermal conductivity is better, and the time to reach the maximum set temperature of 60°C is shorter, indicating that the successful construction of the three-dimensional thermal conductive network is beneficial to improving the thermal conductivity and heat dissipation performance.
[0120] EP and BN m @EP / EP-CNTs composite dielectric properties: dielectric constant diagram Fig.10 shown by Fig.10It can be seen that epoxy resin has the highest dielectric constant. However, CNTs in the composite material are conductive, so the dielectric constant of the composite material is lower than that of EP. Therefore, the test results show that EP, 3D-BN m @The dielectric constant of EP / EP-CNTs (0wt%-2wt%) dropped from 4.05 of EP to 3.91, with little change. m @EP / EP-CNTs composites still have excellent electrical insulation properties.
[0121] EP and BN m @EP / EP-CNTs composite dielectric properties: dielectric loss diagram Fig.11 shown by Fig.11 It can be seen that the dielectric loss is tested at a fixed frequency of 1000HZ. As shown in the figure, the dielectric loss of the composite material gradually increases. This is because both dipole polarization and interface polarization consume energy, resulting in polarization loss. Among them, EP has the smallest dielectric loss, and 3D-BN has the smallest dielectric loss. m The dielectric loss of @EP / EP-CNTs increases from 0.00378 to 0.0085 with the increase of CNTs filler content and the influence of the three-dimensional thermal conductive network structure, with a small range of variation and no significant effect. m @EP / EP-CNTs composites still have excellent electrical insulation properties.
[0122] EP and BN m @EP / EP-CNTs composite material breakdown field strength diagram Fig.12 shown by Fig.12 It can be seen that the destructive field strength of EP is 24.37 kV / mm, while that of 3D-BN m @EP / EP-2wt%CNTs composite material has a destructive field strength reduced to 21.75kV / mm. This is because BN m It has a high intrinsic breakdown strength and is evenly impregnated in the EP matrix. Its excellent insulation properties will become an obstacle to charging and transportation. Structural defects such as gaps will appear, and the conductive particles between the interface and the composite material will often cause changes in the electric field concentration and the electrolytic tension, thereby generating defects and weakening the destructive field strength of the composite material. The addition of trace CNTs has little effect on the electric field strength. Therefore, 3D-BN m @EP / EP-CNTs composites still have excellent electrical insulation properties.
Claims
1. A 3D BN constructed by electrostatic direct writing 3D printing m @EP / EP-CNTs composite material method, characterized in that, The following steps are involved: Step 1: Stir epoxy resin, photoinitiator and diluent evenly under light-proof conditions, then add flake modified hexagonal boron nitride (BN m ), continue to stir in dark until uniform, to obtain slurry; Step 2: Slowly inject the slurry prepared in step 1 into the syringe and degas. Step 3: Install the degassed syringe on the 3D printer head, use direct ink writing (DIW) 3D printing technology to print and perform UV curing to obtain a three-dimensional mesh skeleton; Step 5: Stir the epoxy resin and curing agent evenly in an oil bath at 60°C-80°C, then add the carbon nanotubes, continue stirring until evenly mixed, then add the accelerator, continue stirring, degas, and obtain a glue solution; Step 6: Place the three-dimensional mesh skeleton in a preheated mold, quickly pour in the glue solution to immerse the skeleton in it, and after gradient heating and curing, obtain the composite material.
2. The method according to claim 1, characterized in that: The mass ratio of epoxy resin, photoinitiator, diluent and flake modified hexagonal boron nitride is 100:2:1:25, the photoinitiator is triarylsulfonium salt cationic photoinitiator 1176, and the diluent is xylene.
3. The method according to claim 1, characterized in that: In step 1, octadecyltrimethylammonium bromide is used to modify the flake hexagonal boron nitride.
4. The method according to claim 1, characterized in that The process parameters of DIW 3D printing technology are as follows: the inner diameter of the nozzle is 0.3 mm; the printing speed is 30 mm / s; the layer thickness is 0.5 mm; and the ambient temperature is room temperature.
5. The method according to claim 1, characterized in that: UV curing process parameters: 300w light efficiency, 365nm wavelength.
6. The method according to claim 1, characterized in that: The epoxy resin in step 1 and step 5 is bisphenol A epoxy resin E51.
7. The method according to claim 1, characterized in that: The mass ratio of epoxy resin to curing agent is 100:72, the amount of accelerator is 1% of the total mass of epoxy resin and curing agent; the carbon nanotube accounts for 0%-2% of the mass of epoxy resin; the curing agent is methyl hexahydrophthalic anhydride, and the accelerator is nitrogen-nitrogen dimethyl benzylamine.
8. The method according to claim 1, characterized in that: The mold preheating temperature is 60℃-80℃.
9. The method according to claim 1, characterized in that: The gradient temperature curing was set as follows: curing at 80°C-100°C for 1.5 hours, heating to 120°C-130°C, curing for 1.5 hours, and then heating to 140°C-160°C, curing for 2 hours.
10. A composite material prepared by the method according to any one of claims 1 to 9.